The Syriac double verb, its reality and meanings Semitic comparative study (Journal of the College of Basic Education, 2022)
Grammarians and researchers differed on the naming of the double verb, some of them call it the weak verb (), and some of them call it the double verb, and some of them call it the double verb. The grammatical indication that removes confusion is that the double verb is called so as not to confuse the scholars, researchers and students of knowledge, which is what is meant by the double nomenclature weight (fa’a) or the double weight of the eye (verb), knowing that the weight of the triple double verb in the morphological scale is (verb) because that shid = stressed and so on... So the research will be conducted by calling our verb multiplier.